Evaluation of Urban Green Spaces in Terms of User Satisfaction: A Case Study on Serik / Antalya - Rifat Olgun; Emine Kahraman; Nihat Karakuş (Turkish Journal of Agriculture: Food Science and Technology)
With their urban green spaces, cities enable people to live a comfortable social and physical life. However, recent population growth and fast urbanization have resulted in a decline of green areas in urban areas over time. Cities' livability rate is being reduced as a result of this situation. In addition to these quantitative values of urban green areas, their qualitative characteristics also have an important place in terms of the benefits they provide to cities and their users. The aim of the research is to determine the user satisfaction level of the urban green areas and the user opinions about the urban green areas of the city of Serik. In this context, a survey was conducted on a voluntary basis with 384 individuals using the urban green areas of the city of Serik. As a result of the analysis of the data obtained from the questionnaire forms, the user satisfaction levels, opinions, and suggestions for the urban green areas of the city of Serik were determined. In this direction, suggestions have been developed to increase the qualitative value and user satisfaction of urban green areas in the city of Serik.